Occular Drug Delivery System: A Novel Review with Applications (Asian Journal of Pharmaceutics (AJP), 2025)
Among the many drug delivery systems, ocular drug delivery system,maintaining a therapeutic drug level atthe site of action, is one of the most difficult issues pharmaceutical researchers and associates face for a longtime. Programmable medication delivery mechanisms provide a lot benefits, positive aspects in standard amountmethods within regards for reduce dosing frequency, nontoxic and biocompatible, either water-friendly as well asa lipophilic substances had been enclosed, targeted drug delivery can be achieved, improves dissolution, thereforeimproving an accessibility of substances, large scale production is possible, intended medication delivery insimple exterior alterations, stops deterioration of a lipophilic substances and provides over time equilibrium,prevents medication explosion upon storage, prepared employing a combine of a solid and a liquid lipids as anessential matrices, clear, thermodynamically secure formulations with a droplet size of 100 nm, prevents generaldistribution, enhances beneficial effectiveness, protects drug form deterioration, elevates intercellular penetration,thus enhancing absorption by using niosomes, discomes, cubosomes, nanowafers, dendrimers, polymer-drugconjugates, nanosuspensins, nanoemulsions, polymeric nanomiccelles, surfactant nanomicelles, polyion complexnanomicelles, nanostructure lipid carriers, solid lipid carriers, liposomes, polymeric nanoparticles, viscosityenhancers, produrg, ocular iontophoresis, hydrogels, nanoparticles, contact lens, microneedles, in situ gellingsystem, microemulsion, sonophoresis, phototherapy, and various medications through implants. These numerousdesigns have been made for some of the special routes of drug delivery such as Intravitreal administration,intracameral, perilocular, suprachoroidal, subconjunctiva, topical, and systemic with various mechanisms.The marketed preparations, such as natamycin solid lip nanoparticles, ciprocin, dex in isotonic acetate buffer,ophthalmic emulsion, napafenacc ophthalmic suspension, etc., are available in various modes of drug delivery.